2023
DOI: 10.1021/acs.jcim.2c01497
|View full text |Cite
|
Sign up to set email alerts
|

Quasiclassical Trajectory Simulation as a Protocol to Build Locally Accurate Machine Learning Potentials

Abstract: Direct trajectory calculations have become increasingly popular in recent computational chemistry investigations. However, the exorbitant computational cost of ab initio trajectory calculations usually limits its application in mechanistic explorations. Recently, machine learning-based potential energy surface (ML-PES) provides a powerful strategy to circumvent the heavy computational cost and meanwhile maintain the required accuracy. Despite the appealing potential, constructing a robust ML-PES is still chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…However, building a robust ML-PES comes with its own set of hurdles, as the training set for the potential energy surface must sufficiently cover an all-encompassing configuration space. In a landmark breakthrough in 2023, X. Hong and T. Hou charted a pioneering path [90], as shown in Figure 11. They proposed an innovative approach involving the use of quasiclassical trajectory (QCT) calculations when the required properties can be determined by localised sampling of the configuration space.…”
Section: Prediction Of Reactivity Of Chemical Reactionsmentioning
confidence: 99%
“…However, building a robust ML-PES comes with its own set of hurdles, as the training set for the potential energy surface must sufficiently cover an all-encompassing configuration space. In a landmark breakthrough in 2023, X. Hong and T. Hou charted a pioneering path [90], as shown in Figure 11. They proposed an innovative approach involving the use of quasiclassical trajectory (QCT) calculations when the required properties can be determined by localised sampling of the configuration space.…”
Section: Prediction Of Reactivity Of Chemical Reactionsmentioning
confidence: 99%
“…In studying reaction dynamics, such training sets can sometimes be large. 41 However, a study by Zhang et al demonstrated that the size of the training set can be reduced by limiting the degree of freedom in the reaction space. 41 This can be achieved by running quasiclassical direct dynamics trajectories initialized at TS and proceeding in the direction of forming products.…”
Section: ■ Introductionmentioning
confidence: 99%
“…41 However, a study by Zhang et al demonstrated that the size of the training set can be reduced by limiting the degree of freedom in the reaction space. 41 This can be achieved by running quasiclassical direct dynamics trajectories initialized at TS and proceeding in the direction of forming products. To the best of our knowledge, an approach using a ML-based force field for reactions with PTSB has not been reported yet.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation